Inferences on hydrogen bond networks in water from isopermitive frequency investigations. (12th July 2018) - Geethu, P M; Ranganathan, Venketesh T; Satapathy, Dillip K
Abstract: Intermolecular hydrogen bonds play a crucial role in determining the unique characteristics of liquid water. We present low-frequency (1 Hz–40 MHz) dielectric spectroscopic investigations on water in the presence and absence of added solutes at different temperatures from 10 °C to 60 °C. The intersection points of temperature dependent permittivity contours at the vicinity of isopermitive frequency (IPF) in water are recorded and its properties are presumed to be related to the extent of hydrogen bond networks in water. IPF is defined as the frequency at which the relative permittivity of water is almost independent of temperature. The set of intersection points of temperature dependent permittivity contours at the vicinity of IPF are characterized by the mean and root-mean-square deviation/standard deviation associated with IPF. The tunability of M IPF by the addition of NaCl and MgCl2 salt emphasizes the strong correlation between the concentration of ions in water and the M IPF . The is surmised to be related to the orientational correlations of water dipoles as well as to the intermolecular hydrogen bond networks in water. Further, alterations in is observed with the addition of kosmotropic and chaotropic solutes into water and are thought to arise due to the restructuring of hydrogen bond networks in water in presence of added solutes. Notably, the solute induced reconfiguration of hydrogen bond networks in water or often-discussed structure making/breaking effects of the added solutes in water can be inferred, albeit qualitatively, by examining the M IPF and . Further, the Gaussian deconvoluted OH-stretching modes present in the Raman spectra of water and aqueous solutions of IPA and DMF strongly endorses the structural rearrangements occurring in water in presence of kosmotropes and chaotropes and are in line with the results derived from the root-mean-square deviation in IPF.